2017
DOI: 10.4103/jioh.jioh_171_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a glaze polishing technique for pigmented denture acrylic resin submitted to thermocycling and disinfection

Abstract: IntroductIon Acrylic resin is the most commonly used material to manufacture conventional removable prostheses; it is a low-cost material, has good adaptability to oral tissue, it is easy to manipulate, and possesses satisfactory esthetic characteristics. [1-3] The acrylic resin must mimic the soft tissue features to provide an excellent esthetic outcome, [4] and there are two techniques to do so: An extrinsic characterization in which the pigments are added after the polymerization process; and an intrinsic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Resistance to the micro crack because of the De-flex acrylic resin contains extra hard fibers in the material. The outcomes of the current researches are in agreement with Goiato et al (22) the glaze polished groups presented higher surface hardness results. Also in agreement with Sesma et al (23) glaze crack may have happened due to the inflexibility that the glaze layer need after the heating of light and an elevated surface rigidity and a reduction in the influence strength and transverse winding strength of resins surface coated with a surfaces glaze.…”
Section: Discussionsupporting
confidence: 92%
“…Resistance to the micro crack because of the De-flex acrylic resin contains extra hard fibers in the material. The outcomes of the current researches are in agreement with Goiato et al (22) the glaze polished groups presented higher surface hardness results. Also in agreement with Sesma et al (23) glaze crack may have happened due to the inflexibility that the glaze layer need after the heating of light and an elevated surface rigidity and a reduction in the influence strength and transverse winding strength of resins surface coated with a surfaces glaze.…”
Section: Discussionsupporting
confidence: 92%
“…A study has found that a glossy, smooth surface prevents discolouring films from forming, impedes plaque formation, and assists the removal of plaque [17]. The structure of the acrylic resin in combination with the accumulation of substances can also impact the colour stability, particularly if the material has a higher surface roughness [8,38]. Polychronakis et al [36] assessed the impact that denture cleaners had on the surface roughness, colour and gloss of nylon and heat-polymerised acrylic denture base resins before and after immersion in test liquids for 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al [18] found that there was a positive correlation between colour change in acrylic resins and immersion time as a result of monomer leaching out and the absorption of water. Furthermore, Goiato et al [38] concluded that any monomer released during storage could interact with the glaze layer, resulting in increased colour change. The primary discolouring mechanism is likely to be the sorption of liquids (solutions) [9].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a smooth surface prevents the formation of discolouring films, affects plaque formation and facilitates its removal [10]. The composition of the acrylic resin and built-up substances can also influence the colour stability, especially if the surface roughness is higher [23]. Polychronakis et al evaluated the influence of denture cleaners on colour, surface roughness and gloss of nylon and heat polymerized acrylic denture base resins before and after 30 days of immersion [12].…”
Section: Discussionmentioning
confidence: 99%
“…Goiato et al found that the release of monomer during storage could interact with the glaze layer and cause increased colour change [23]. In addition, residual monomer can react with pigments inside the polymer, causing further colour changes [3].…”
Section: Discussionmentioning
confidence: 99%